The White Page Burns - Oksana Vasyakina (The February Journal)
This poetic essay considers how politics changes optics of reading poems written more than fifty years ago. The author compares her feelings about Vsevolod Nekrasov’s text 'I’m silent/stay silent’ before and after the events of February 24, 2022.